Dysgraphia in Relation to Cognitive Performance in Patients with Alzheimer’s Disease - Onofri, Emanuela; Mercuri, Marco; Salesi, MariaLucia; Ferrara, Salvatore; Troili, Giulia Maria; Simeone, Claudio; Ricciardi, Max Rapp; Ricci, Serafino; Archer, Trevor (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Dysgraphia has been observed in patients presenting mild to moderate levels of Alzheimer’s disease (AD) in several studies. In the present study, 30 AD patients and 30 matched healthy controls, originating from the Lazio region, Rome, Italy, were examined on tests of letter-writing ability and cognitive performance over a series of 10 test days that extended over 19 days (Test days: 1, 3, 5, 7, 9 11, 13, 15, 17, and 19). Consistent deficits by the AD patients over the initial cognition test (PQ1), 2nd cognition test (PQ2) and the difference between them (D∆), expressing deterioration, and writing-time compared the group of healthy control subjects were obtained. Furthermore, the performances of the AD patients on the PQ1, D∆ and writing-time, but not the PQ2, tests deteriorated from the 1st five days of testing (Days 1-9) to the 2nd five days (11-19). Both AD patients’ and healthy controls’ MMSE scores were markedly and significantly correlated with performance of PQ1, writing-time and PQ2. The extent of dysgraphia and progressive deficits in the AD patients implicate multiple brain regions in the loss of functional integrity.